Demokrasi di Indonesia Mewujudkan Kedaulatan Rakyat - Erla Sharfina Permata Noor; Ahmadi Hasan; Masyithah Umar (Sharia Journal and Education Center Publishing, 2023)
Abstract Since the reform era in 1998, democracy has been highly valued and implemented as the governing system in Indonesia. The concept of popular sovereignty has become the main principle in democracy, where the power of governance rests in the hands of the people as the highest authority. However, realizing popular sovereignty in the complex context of Indonesia is not an easy task. This study examines various aspects that influence the implementation of democracy in Indonesia, such as the role of political parties, mass media, elections, and public participation in political decision-making. Additionally, this study also discusses the challenges and obstacles faced in achieving popular sovereignty in Indonesia, including corruption, restrictions on freedom of expression from a human rights perspective, lack of transparency, controversial money politics in elections, intolerance, discrimination, and social injustice. Overcoming these challenges requires collaborative efforts among the government, society, and all elements of the nation. This research aims to provide a deep understanding of the journey of democracy in Indonesia in realizing popular sovereignty and to encourage active contributions in strengthening democracy and preserving the integrity of the Indonesian nation. Keywords: Democracy, sovereignty, people Abstrak: Sejak reformasi tahun 1998, demokrasi telah menjadi sistem pemerintahan yang dijunjung tinggi di Indonesia. Konsep kedaulatan rakyat menjadi prinsip utama dalam demokrasi, di mana kekuasaan pemerintahan berada di tangan rakyat sebagai pemilik kekuasaan tertinggi. Namun, mewujudkan kedaulatan rakyat dalam konteks yang kompleks seperti Indonesia bukanlah hal yang mudah. Penelitian ini mengkaji berbagai aspek yang mempengaruhi pelaksanaan demokrasi di Indonesia, seperti peran partai politik, media massa, pemilihan umum, dan partisipasi masyarakat dalam pengambilan keputusan politik. Selain itu, penelitian ini juga membahas tantangan dan hambatan yang dihadapi dalam mewujudkan kedaulatan rakyat di Indonesia, termasuk praktik korupsi, keterbaratasan kebebasan berekspresi dal persfektif hak asasi manusia, kurangnya transparansi, adanya money politic dalam pemlilihan umum yang kontroversial, intoleransi, diskriminasi, dan ketidakadilan sosial. Untuk mengatasi tantangan tersebut, diperlukan upaya kolaboratif antara pemerintah, masyarakat, dan seluruh elemen bangsa. Penelitian ini diharapkan dapat memberikan pemahaman yang mendalam tentang perjalanan demokrasi di Indonesia dalam mewujudkan kedaulatan rakyat, serta mendorong kontribusi aktif dalam memperkuat demokrasi dan menjaga keutuhan negara Indonesia. Kata Kunci: Demokrasi, kedaulatan, rakyat